PRARANCANGAN PABRIK AMONIUM SULFAT DARI AMONIA DAN ASAM SULFAT KAPASITAS 250.000 TON/ TAHUN - , HUTAMI INSAN PERWITA, Ir. Suprihastuti Sri Rahayu, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this 250.000 ton/year-capacity ammonium sulphate from ammonia and sulfuric acid preliminary plant design uses neutralization process. Neutralization process is one of dry process because ammonium sulphate product yielded has relatively low water content. The reactor type used in the process is spray reactor operated in pressure of 5 atm and temperature of 143 Â°C. The amount of ammonium sulphate product yielded is 31565,6566 kg/hour. It is expected to fulfill ammonium sulphate fertilizer local needs. In this process there is no side products produced. The amount of raw materials needed to produce 31565,6566 kg/hour are 8049,24 kg/hour of ammonia dan 23221,6592 kg/hour of sulfuric acid. Supporting materials used in this process are water and air. The decided location in this ammonium sulphate from ammonia and sulfuric acid preliminary plant design is Bontang, Kalimantan Timur. This decision is based on the rawmaterial- oriented judgement, in this case is ammonia. Ammonia is provided by PT. Kaltim Parna Industri, whereas sulfuric acid is provided by PT. Petrokimia Gresik. Ammonia handling and storage is considered more hazardous than sulfuric acid because it sometimes needs refrigeration system or high-pressurized vessel. The total of area planned to build is around 40.000 m2. The total of workers planned to recruited are 162 people. The capital required to design this plant is predicted to be around Rp. 118.592.358.900,7180 for the fixed capital and Rp 241.685.642.514,4080 for the working capital. By taking rupiah to dollar exchange rate of Rp.9.795 it can be seen that the value of fixed and working capitals are US$ 12.107.438,3800 and US$ 24.674.389,23 as follow. Economic evaluation shows its percent return of investment before taxes (ROIb) is 97,11%. This return of investment value after taxes (ROIa) is 48,56%. The payout time before taxes (POTb) is 0,93 year, whereas its value after taxes (POTa) is 1,71 year. The Break Even Point (BEP) is 41,07%. This BEP value shows that this plant design can still be considered as potentially interesting to invest since it is still in a interesting-to-invest BEP range, 30 â 60%. Economic evaluation shows that the plant would earn profit before taxes as much as Rp 115.166.003.008 per year. It leads us that the 250.000 ton/year capacity ammonium sulphate preliminary design plant is quite interesting to be evaluated further.